THE CIRCULATION OF A MELODIC TYPE OF SCHOLARLY CAROL FROM THE LAND OF THE FORESTERS, HUNEDOARA - STAN, Alina-Lucia (Studia Universitatis Babes-Bolyai Musica, 2022)
The religious carol or with scholarly influence is a musical typological category that is less addressed in the specialized music literature, especially entering the area of interest of religious music. Due to this provenance and a relatively recent evolution in time (only a few hundred years), we find a distinct melodicity compared to the authentic Romanian carol. Melodic variants identified mainly in the Land of the Foresters, Hunedoara, circulate in southern Transylvania on religious carol texts, being collected in the field more than 100 years ago (Bartók, 1913). By the number of variations, we realize that it is a very beloved song, easy to remember, which closes the cycle of the Winter Holidays (Epiphany). The present research aims to identify the melodic variants of this scholarly carol, as well as, most importantly, its spread within other folk genres: old-style songs and dance songs.